IGREJA UNIVERSAL DO REINO DE DEUS NA ÁFRICA SUBSAARIANA: IMPLANTAÇÃO, EXPANSÃO E TRANSNACIONALIZAÇÃO - Bowane, Adrien Gyato (2014)
The purpose of this paper is to show the implementation strategies and the expansion of the Universal Church of the Kingdom of God (UCKG) in sub-Saharan Africa, while taking into account the rapid growth of Pentecostalism in the world and the context of religious trans-nationalization. The UCKG is a Brazilian Pentecostal Church that emerged in 1977 and expanded into many countries worldwide. It is present in 39 countries in sub-Saharan Africa concentrating mostly in large cities. Several factors prove its growth and expansion in Africa, among other factors syncretism, i.e., the ability to adapt to African culture. The other factors are: social visibility (especially through the use of media and social assistance), the political secrecy, the practice of exorcism, prosperity discourses, the friendship and partner-ship with African governments, their anti-ecumenical attitude and the adoption of an Episcopal organization. This paper brings some discussions regarding Pentecostalism and neo-Pentecostalism in Sub-Saharan Africa, African Independent Churches (AIC) and the presence of Christianity in Africa since the very beginning.